Mood, sleep and pain comorbidity outcomes in cannabis dependent patients: Findings from a nabiximols versus placebo randomised controlled trial. (1st May 2022) - Montebello, Mark; Jefferies, Meryem; Mills, Llewellyn; Bruno, Raimondo; Copeland, Jan; McGregor, Iain; Rivas, Consuelo; Jackson, Melissa A.; Silsbury, Catherine; Dunlop, Adrian; Lintzeris, Nicholas; ,
Abstract: Background: Mood, sleep and pain problems are common comorbidities among treatment-seeking cannabis-dependent patients. There is limited evidence suggesting treatment for cannabis dependence is associated with their improvement. This study explored the impact of cannabis dependence treatment on these comorbidities. Methods: This is a secondary analysis from a 12-week double-blind placebo-controlled trial testing the efficacy of a cannabis agonist (nabiximols) against placebo in reducing illicit cannabis use in 128 cannabis-dependent participants. Outcome measurements including DASS-21 (Depression, Anxiety, and Stress subscales); Insomnia Severity Index (ISI); and Brief Pain Inventory (BPI), were performed at weeks 0, 4, 8, 12 and 24. Each was analysed as continuous outcomes and as binary cases based on validated clinical cut-offs. Results: Among those whose DASS and ISI scores were in the moderate to severe range at baseline, after controlling for cannabis use, there was a gradual decrease in severity of symptoms over the course of the trial. BPI decreased significantly until week 12 and then rose again in the post-treatment period during weeks 12–24. Neither pharmacotherapy type (nabiximols vs placebo) nor number of counselling sessions contributed significant explanatory power to any of the models and were excluded from the final analyses for both continuous and categorical outcomes. Conclusions: Participants in this trial who qualified as cases at baseline had elevated comorbidity symptoms. There was no evidence that nabiximols treatment is a barrier to achieving reductions in the comorbid symptoms examined. Cannabis dependence treatment reduced illicit cannabis use and improved comorbidity symptoms, even when complete abstinence was not achieved. Highlights: Depression, anxiety, stress, stressand sleep disturbance symptoms decreased with cannabis dependence treatment. Pain symptoms improved only in the treatment period for cannabis dependence. Participants in this trial who qualified as cases at baseline had elevated comorbidity symptoms. There was no evidence that nabiximols treatment is a barrier to achieving reductions in the comorbid symptoms examined. Abstinence is not required to achieve improvements in comorbid mood, sleep and pain symptoms.